Community Asset Mapping in Indonesian Local Micro Enterprise Empowerment: Insights from Sukamantri Village - Kunyati, Siti Anah; Radianti, Jaziar (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
This study aims to assess community resources for development and to pinpoint the challenges faced by palm sugar micro-businesses. A qualitative approach was used, involving ten participants. Data was gathered through observation, in-depth interviews, and documentation. The results reveal a strong sense of community and a significant entrepreneurial drive among residents. However, there is untapped potential in environmental resources for land development that could support the cultivation of sugar palm trees, which are currently endangered. On the other hand, economic resources, such as the palm sugar marketing network, production enhancement, and sourcing of raw materials, are underdeveloped due to community isolation, reliance on traditional markets, and a lack of knowledge about digital marketing. The lack of management institutions, capacity-building programs, social network support, and government assistance greatly hinders the growth of these resources and the micro-businesses. To improve the capabilities of palm sugar micro-entrepreneurs in Sukamantri Village, it is crucial to tackle several key issues, including poor business management practices, weaknesses in local institutions, limited networking opportunities, and challenges related to funding and support. The researchers suggest that local government and the private sector should focus on support programs, enhancing the management and production processes of palm sugar micro-enterprises.